Admissions and surgery as indicators of hospital functions in Sierra Leone during the west-African Ebola outbreak - Håkon A. Bolkan; Alex van Duinen; Mohammed Samai; Donald Alpha Bash-Taqi; Ibrahim Gassama; Bart Waalewijn; Arne Wibe; Johan von Schreeb (BMC, 2018)
Abstract Background In an attempt to assess the effects of the Ebola viral disease (EVD) on hospital functions in Sierra Leone, the aim of this study was to evaluate changes in provisions of surgery and non-Ebola admissions during the first year of the EVD outbreak. Methods All hospitals in Sierra Leone known to perform inpatient surgery were assessed for non-Ebola admissions, volume of surgery, caesarean deliveries and inguinal hernia repairs between January 2014 and May 2015, which was a total of 72 weeks. Accumulated weekly data were gathered from readily available hospital records at bi-weekly visits during the peak of the outbreak from September 2014 to May 2015. The Mann-Whitney U test was used to compare weekly median admissions during the first year of the EVD outbreak, with the 20 weeks before the outbreak, and weekly median volume of surgeries performed during the first year of the EVD outbreak with identical weeks of 2012. The manuscript is prepared according to the STROBE checklist for cross-sectional studies. Results Of the 42 hospitals identified, 40 had available data for 94% (2719/2880) of the weeks. There was a 51% decrease in weekly median non-Ebola admissions and 41% fewer weekly median surgeries performed compared with the 20 weeks before the outbreak (admission) and 2012 (volume of surgery). Governmental hospitals experienced a smaller reduction in non-Ebola admissions (45% versus 60%) and surgeries (31% versus 53%) compared to private non-profit hospitals. Governmental hospitals realized an increased volume of cesarean deliveries by 45% during the EVD outbreak, thereby absorbing the 43% reduction observed in the private non-profit hospitals. Conclusions Both non-Ebola admissions and surgeries were severely reduced during the EVD outbreak. In addition to responding to the EVD outbreak, governmental hospitals were able to maintain certain core health systems functions. Volume of surgery is a promising indicator of hospital functions that should be further explored.